The Influence of Price and Promotion on Consumers’ Repurchase Intention in the Double Date Program on Shopee Marketplace: A Study on Shopee Customers in Pontianak City - Rama Yupani; Ananda Archie (SAINTIS Publishing, 2025)
This study aims to evaluate the influence of price and promotion variables on consumers’ repurchase intention during the double-date promotional program on the Shopee platform, focusing on users in Pontianak City. The research adopts an associative quantitative method, applied through a case study involving active Shopee users in the region. Primary data were collected through questionnaires distributed to 150 selected respondents using a purposive sampling technique, while secondary data were obtained from official sources such as Shopee reports, Katadata, and Statista. The collected data were analyzed using multiple linear regression with the aid of IBM SPSS version 25, accompanied by validity, reliability, and classical assumption tests to ensure the robustness of the analytical model. The results reveal that both price and promotion have a positive and significant effect on consumers’ repurchase intention, whether examined jointly or individually. The coefficient of determination (R² = 0.385) indicates that 38.5% of the variation in repurchase intention is explained by these two factors. This finding highlights that rational pricing strategies and attractive promotional activities such as discounts, cashback programs, and interactive features like Shopee Live play an important role in strengthening customer loyalty and encouraging repeat purchases. Theoretically, this study contributes to the understanding of consumer behavior in the digital marketing era, particularly in the context of large-scale e-commerce promotional campaigns. Practically, the findings provide strategic insights for marketplace companies in formulating adaptive pricing and promotional policies aimed at enhancing customer retention and improving competitiveness within the digital economy landscape.